2021
DOI: 10.1088/1361-6528/abeb3c
|View full text |Cite
|
Sign up to set email alerts
|

Numerical homogenization of thermal conductivity of particle-filled thermal interface material by fast Fourier transform method

Abstract: Thermal interface material (TIM) is pivotal for the heat dissipation between layers of high-density electronic packaging. The most widely used TIMs are particle-filled composite materials, in which highly conductive particulate fillers are added into the polymer matrix to promote heat conduction. The numerical simulation of heat transfer in the composites is essential for the design of TIMs; however, the widely used finite element method (FEM) requires large memory and presents limited computational time for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…To this end, we have employed the FFT algorithm-based numerical method to solve the heat transfer problems in the particulate composites in our previous work. We discussed the effect of ITRs on the effective TCs, and pointed out that the experimental measured TC of the composite can be reproduced by selecting the proper ITRs, confirming the relationships between ITRs and TCs . Those facts ensure to get the exact solution of the TC of a composite material when its basic attributes are given as input parameters with arbitrary values (such as the intrisic TCs of polymer and fillers, the ITRs between ingredients inside the composite).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have employed the FFT algorithm-based numerical method to solve the heat transfer problems in the particulate composites in our previous work. We discussed the effect of ITRs on the effective TCs, and pointed out that the experimental measured TC of the composite can be reproduced by selecting the proper ITRs, confirming the relationships between ITRs and TCs . Those facts ensure to get the exact solution of the TC of a composite material when its basic attributes are given as input parameters with arbitrary values (such as the intrisic TCs of polymer and fillers, the ITRs between ingredients inside the composite).…”
Section: Discussionmentioning
confidence: 99%
“…To solve the equation and determine the temperature distribution in the composite system, the periodic boundary conditions are employed on the domain boundary ∂Ω. In our previous report, the ITR is taken into account as a thin additional phase which is different from either the filler or the matrix, and a FFT-based iterative scheme in terms of polarization has been utilized to solve the mathematical equations of the heat transfer . In this work, if two neighboring voxels correspond to different materials, the interface between them is represented by an imperfect interface through which the temperature is continuous, while the heat flux suffers a jump in the normal direction, as shown in Figure . [ T l ] false| bold-italicx = bold-italicx * = 0 [ k T l x i ] false| bold-italicx = bold-italicx * = prefix− δ i l false[ k false] bold-italicx = bold-italicx * goodbreak0em2em⁣ normalf normalo normalr .25em i = 1,2.3 where δ il is the Kronecker symbol δ i l = { lefttrue 1 , f o r i = l , 0 , …”
Section: Methodsmentioning
confidence: 99%
“…GeoDict calculates the TC tensors based on the so-called explicit jump immersed interface approach, which solves the equations in parallel by combing the fast Fourier transform (FFT) and GiGGStab methods. We have recently shown that the approach dramatically reduces the computational time and requirement of memory without losing precision compared with the finite element modeling, which enables the efficient and accurate high-throughput calculations [28]. The input parameters for the numerical simulations are the TCs of the fillers, the ITR between the fillers and silicone matrix (ITR f −p ), and the ITR between the fillers (ITR f −f ).…”
Section: Determination Of Quantitative Relationship Between Itr and T...mentioning
confidence: 99%
“…Although the experimental approach to improve the thermal conductivity of TIM is important, numerical studies are necessary to better understand the heat-transfer mechanism between filler particles and matrix materials and optimize filler-matching methods. , The finite element method (FEM) is a full-field numerical simulation method that has been used in the prediction and optimization of the effective thermal conductivity of TIMs. However, the FEM generally has a higher computational cost when simulating the TIM with a real microstructure, and the larger particle size distribution gradient of multiscale particles will result in a large number of meshes, especially at a high volume particle-packing fraction. Therefore, it is difficult for the FEM to realize the multivariable problem of multiscale particle size matching optimization.…”
Section: Introductionmentioning
confidence: 99%